The Effect of E-HRM Implementation on Employee Performance in Manufacturing Companies - Muchsinati, Evi Silvana; Ella, Monica; Sentoso, Antony (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to study the impact of e-human resources management (e-HRM) on employee performance and determine the relationship between job satisfaction in manufacturing industrial companies in the city of Batam. This research has seven variables studied, using samples from PT. Venturindo Jaya Batam, PT. Sat Nusapersada, Tbk. and PT. LKD Multi Industri, with a total of 452 respondents. Data was obtained from distributing questionnaires using a Likert scale, and the analysis tools used were SmartPLS and SPSS. The results found that e-HRM has evidence that it can increase job satisfaction and employee performance in manufacturing companies in the city of Batam. What can be seen from the results is that there are only two that have a positive and significant effect on employee performance and employee job satisfaction is not significant.